2012
DOI: 10.1111/j.1440-1746.2011.06958.x
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab or cyclosporine for acute severe ulcerative colitis: A retrospective analysis

Abstract: Infliximab improved clinical outcomes compared to the previous use of intravenous cyclosporine in patients admitted with steroid-refractory acute severe UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Although both ciclosporin and infliximab were effective in steroid-resistant UC, results did not agree which drug was better. [32][33][34][35] One small retrospective study 34 of 38 patients with acute UC resistant to steroids showed a higher rate of colectomy in patients who received ciclosporin (63% and 68% at 3 and 12 months, respectively) than in those who received infliximab (21% and 37% at 3 and 12 months, respectively); there was no significant difference between groups in adverse events (AEs) or steroid dependence. A prospective study 36 found the colectomy-free rate at discharge, and at 3 and 12 months from admission, was significantly higher in patients who had infliximab as a rescue therapy (n = 45) compared with those who had ciclosporin (n = 38).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although both ciclosporin and infliximab were effective in steroid-resistant UC, results did not agree which drug was better. [32][33][34][35] One small retrospective study 34 of 38 patients with acute UC resistant to steroids showed a higher rate of colectomy in patients who received ciclosporin (63% and 68% at 3 and 12 months, respectively) than in those who received infliximab (21% and 37% at 3 and 12 months, respectively); there was no significant difference between groups in adverse events (AEs) or steroid dependence. A prospective study 36 found the colectomy-free rate at discharge, and at 3 and 12 months from admission, was significantly higher in patients who had infliximab as a rescue therapy (n = 45) compared with those who had ciclosporin (n = 38).…”
Section: Review Of Literaturementioning
confidence: 99%
“…We used the electronic search strategies checklist of the Cochrane Collaboration. 31 We identified nine observational studies and one RCT [32][33][34][35][36][37][38][39][40][41] that compared the efficacy and safety of ciclosporin with those of infliximab ( Table 1). Although both ciclosporin and infliximab were effective in steroid-resistant UC, results did not agree which drug was better.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Longer term colectomy data suggest that infliximab may be superior to cyclosporine. 28,29 When to Stop Therapy A number of factors (e.g., cost, long-term safety, pregnancy, patient preference) may lead to cessation of TNF-a antagonist therapy. Louis et al 30 performed a prospective study to examine the risk of relapse after discontinuation of infliximab.…”
Section: Management Of Acute Severe Ulcerative Colitismentioning
confidence: 99%
“…[46][47][48][49][50] Although the use of both CsA and IFX has been shown to be effective and safe as rescue therapy compared with placebo in acute severe UC, data regarding head-to-head comparison of CIs and anti-TNF-a agents are limited and based on retrospective observational studies. [51][52][53][54] Mocciaro et al 55 reviewed patients with severe steroid-refractory colitis who had been treated with intravenous CsA (2 mg/kg) or intravenous IFX (5 mg/kg). A total of 65 patients were included: 35 in the CsA group and 30 in the IFX group.…”
Section: Efficacy Of Tac In CDmentioning
confidence: 99%